Human Capital Management, Work Ethics, and Organizational Citizenship Behavior: Keys to Improving the Performance of the Life Insurance Industry - ., Suhardi; Sukati, Inda; Siagian, Mauli; Putra, Ida Bagus Udayana; Husda, Nur Elfi; Shafiq, Dhio (Journal of Cultural Analysis and Social Change, 2025)
Human Capital Management (HCM) has evolved from an isolated and organization-specific practice to a strategic component of a Human Resource Management system, aimed at organizational sustainability; yet, organizations often overlook it. Poor performance among life insurance agents urges the need to identify how HCM and work ethics among insurance agents can be facilitated in the workplace. Human capital management is crucial for enhancing agent performance; however, a centered approach has been the primary focus. This paper emphasizes the significance of considering the interplay between agent-specific performance factors that drive and sustain the performance of life insurance agents. This paper contributes to the emerging human resource management literature, which advocates human capital management as a key human resource development practice designed to enhance agent performance. It also examines the conditions OCB-I and OCB-O that may influence performance in life insurance agents. HCM practices in the life insurance industry can utilize these findings as additional evidence to inform formal/informal strategies within their organizations, promoting better agent performance for both existing and future agents. Human resource practitioners should promote stronger OCB-O and OCB-I, given our findings that agents supported by Human Capital Management experience better performance through better organizational support (helping coworkers/coworker support).